VIVÊNCIAS DE ACADÊMICAS DE ENFERMAGEM EM PESQUISA INSTITUCIONAL COM USUÁRIOS EM HEMODIÁLISE - Patat, Cilene L.; Krüger, Ana P.; Mayer, Bárbara L. D.; Ubessi, Liamara D.; Stumm, Eniva M. F. (Salão do Conhecimento, 2013)
Resumo